Phase behavior of carbon dioxide + medroxyprogesterone acetate system at high pressures - Pinto, L. F. (2013)
In this study the phase equilibrium behavior of the binary system CO2 (1) + medroxyprogesterone acetate (2) was determined. The static synthetic method, using a variable-volume view cell, was employed to obtain the experimental data in the temperature range of (303.15 to 343.15) K and pressures up to about 22 MPa. The mole fraction of medroxyprogesterone acetate varyied in the range from 4.10-5 to 9.10-5. For this system (fluid + solid) and (fluid + fluid + solid) transitions were observed. The phase equilibrium data obtained in this work were modeled using the Peng-Robinson equation of state for describing fluid mixtures, and an expression for the fugacity of pure solid medroxyprogesterone acetate (MPgAc) for representing the solid phase. The thermodynamic model was able to satisfactorily describe the phase behavior of the system investigated.